2022
DOI: 10.1038/s41598-022-08244-7
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic efficiency under visible light of a novel Cu–Fe oxide composite films prepared by one-step sparking process

Abstract: Copper–iron (Cu–Fe) oxide composite films were successfully deposited on quartz substrate by a facile sparking process. The nanoparticles were deposited on the substrate after sparking off the Fe and Cu tips with different ratios and were then annealed at different temperatures. The network particles were observed after annealing the film at 700 °C. Meanwhile, XRD, XPS and SAED patterns of the annealed films at 700 °C consisted of a mixed phase of CuO, γ-Fe2O3, CuFe2O4 and CuFe2O. The film with the lowest ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Figure 5(f) clearly showed that the peaks centered at 1022.32 and 1045.40 eV can be attributed to Zn 2p 3/2 and Zn 2p 1/2 species. Figure 5(e) clearly showed that the peak observed at about 932.74, 952.48eV relates to metallic Cu 2p 3/2 , Cu 2p 1/2 in the alloy [25]. The peaks sited at 712.5 eV in the Fe 2p spectra can be assigned to Fe 3+ and peaks clearly showed at Fig.…”
Section: Structural and Morphological Properties Of The Prepared Nano...mentioning
confidence: 84%
See 2 more Smart Citations
“…Figure 5(f) clearly showed that the peaks centered at 1022.32 and 1045.40 eV can be attributed to Zn 2p 3/2 and Zn 2p 1/2 species. Figure 5(e) clearly showed that the peak observed at about 932.74, 952.48eV relates to metallic Cu 2p 3/2 , Cu 2p 1/2 in the alloy [25]. The peaks sited at 712.5 eV in the Fe 2p spectra can be assigned to Fe 3+ and peaks clearly showed at Fig.…”
Section: Structural and Morphological Properties Of The Prepared Nano...mentioning
confidence: 84%
“…The high-resolution XPS spectra of O 1s were observed at 531.7, 532.45 and 533.3ev After tting with Gaussian-Lorentzian functions, three peaks are discovered in the spectrum; one of them is O 1s peaks at 531.7, corresponding to O 1s in Fe 2 O 3 and absorbed oxygen species [25]. The peaks located at 532.45 and 533.3 eV were related to the oxidized state of Fe (III) [25] respectively. In addition, it is determined that the peak at 532.45 eV re ects H 2 O absorbed in the Fe 2 O 3 nano-boxes and this matched with M. C. Biesinger paper [25].…”
Section: Structural and Morphological Properties Of The Prepared Nano...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh leaves (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) from a healthy guava tree were taken and washed thoroughly with DI water. These leaves were cut into small pieces and put into a beaker containing 300 mL DI water.…”
Section: Preparation Of Guava Leaf Extractmentioning
confidence: 99%
“…CuO/Fe 2 O 3 nanocomposite have been synthesized by a few research groups and explored for various applications like oxidation of n-hexane, oxidation of carbon monoxide, degradation of organic pollutants [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%